Psilocybin intoxication did not affect daytime or sleep-related declarative memory consolidation in a small sample exploratory analysis - Nikolič, Marek; Viktorin, Vojtěch; Zach, Peter; Tylš, Filip; Dudysová, Daniela; Janků, Karolína; Kopřivová, Jana; Kuchař, Martin; Brunovský, Martin; Horáček, Jiří; Páleníček, Tomáš (European neuropsychopharmacology, 2023)
Psilocybin is investigated as a fast-acting antidepressant used in conjunction with psychotherapy. Intact cognitive functions, including memory, are one of the basic conditions of effective psychedelic-assisted therapy. While cognitive and memory processing is attenuated on various domains during psilocybin intoxication, the effect of psilocybin on the consolidation of memories learned outside of acute intoxication is not known. Thus the main aim of the current study was to test the effects of psilocybin on (A) memory consolidation of previously learned material just after the psilocybin session and (B) on overnight memory consolidation the night just after the psilocybin session. 20 healthy volunteers (10 M/10F) were enrolled in a placebo-controlled, double-blind, cross-over design. Effects on declarative memory consolidation in condition (A) The Groton Maze Learning Task and Rey Auditory Verbal Learning Test were used, and for (B) the Pair Associative Learning Test was used. We did not find psilocybin to improve memory consolidation. At the same time, we did not find psilocybin to negatively affect memory consolidation in any of the tests used. This evidence adds to the safety profile for the use of psilocybin.
Keywords: konsolidace paměti; Hallucinogens; Memory Consolidation; Cross-Over Studies; psilocybin; paměť; lidé; spánek; Psilocybin; Sleep; Memory; klinické křížové studie; Humans; halucinogeny